2018
DOI: 10.1016/j.corsci.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal cations on mild steel corrosion in 10 mM Cl− aqueous solution

Abstract: The influences of metal cations on the corrosion of mild steel in 10 mM Claqueous solutions were investigated by electrochemical techniques and immersion tests. Immersion tests and electrochemical impedance spectroscopy (EIS) results showed that Zn 2+ has a significant effect on corrosion inhibition. Surface morphological inspection also showed the smooth surface of specimen immersed in Zn 2+ containing solution. Analysis of X-ray photoelectron spectroscopy showed that Zn 2+ was incorporated in the oxide films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Elucidating the oxidative etching mechanism benefits the design of mental corrosion prevention in industrial applications, sustaining the catalytic nanoparticles from degradation in fuel cells, and synthesis route optimization nanoparticles with desirable size, morphology, structure, and composition during the nucleation−growth stages and postsynthesis treatment, 5−10 particularly for those hard-toprepare nanocrystals via routine routes such as Ag octopod nanocrystals, 11 Ag chiral nanoscrews, 12 and Pd concave nanocubes. 13,14 Oxidative etching reactions occur in a complex solution environment, where multiple factors involved in solution chemistry (like surface ligands, 15 halide ions, 1,16,17 temperature, 18 and pH 8 ) and structural characteristics (such as elemental composition, 6,19,20 structural defects (e.g., twin boundary and vacancy 12,21 ), and coordination number of different sites (e.g., corners, vertexes, and facets 14,22,23 )) all play roles. In the context of solution chemistry, significant progress has been achieved in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elucidating the oxidative etching mechanism benefits the design of mental corrosion prevention in industrial applications, sustaining the catalytic nanoparticles from degradation in fuel cells, and synthesis route optimization nanoparticles with desirable size, morphology, structure, and composition during the nucleation−growth stages and postsynthesis treatment, 5−10 particularly for those hard-toprepare nanocrystals via routine routes such as Ag octopod nanocrystals, 11 Ag chiral nanoscrews, 12 and Pd concave nanocubes. 13,14 Oxidative etching reactions occur in a complex solution environment, where multiple factors involved in solution chemistry (like surface ligands, 15 halide ions, 1,16,17 temperature, 18 and pH 8 ) and structural characteristics (such as elemental composition, 6,19,20 structural defects (e.g., twin boundary and vacancy 12,21 ), and coordination number of different sites (e.g., corners, vertexes, and facets 14,22,23 )) all play roles. In the context of solution chemistry, significant progress has been achieved in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative etching is a fundamental process in many fields such as corrosion science (e.g., mild steel), fuel cells (e.g., Pt-based electrocatalysts degradation), and nanocrystal synthesis (e.g., Au, Pd). Elucidating the oxidative etching mechanism benefits the design of mental corrosion prevention in industrial applications, sustaining the catalytic nanoparticles from degradation in fuel cells, and synthesis route optimization nanoparticles with desirable size, morphology, structure, and composition during the nucleation–growth stages and postsynthesis treatment, particularly for those hard-to-prepare nanocrystals via routine routes such as Ag octopod nanocrystals, Ag chiral nanoscrews, and Pd concave nanocubes. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the change of solution concentration, the Cl À concentration increased from 0.035 mol/L to 0.05 mol/L, and the corrosion rate of SLM 30CrMnSiA steel did not change significantly. When the Cl À concentration is increased to 0.5 mol/L, the corrosion potential is reduced to À751.34 mV SCE , which indicates that the concentration range has a significant effect on the corrosion rate of SLM 30CrMnSiA steel (Lin et al, 2007;Islam et al, 2017). When the concentration of NaCl increased to 1 mol/L, the corrosion potential slightly increased to À723.300 mV SCE , and the corrosion current was 6.601 mA, which indicated that the high chloride ion concentration resulted in the decrease of oxygen content (Lu et al, 2016;Liu et al, 2012).…”
Section: Corrosion Propertiesmentioning
confidence: 99%